Enhanced Terahertz Shielding of MXenes with Nano‐Metamaterials. Issue 5 (16th January 2018) - Choi, Geunchang; Shahzad, Faisal; Bahk, Young‐Mi; Jhon, Young Min; Park, Hyunchul; Alhabeb, Mohamed; Anasori, Babak; Kim, Dai‐Sik; Koo, Chong Min; Gogotsi, Yury; Seo, Minah
Abstract: Terahertz (THz) shielding becomes increasingly important with the growing development of THz electronics and devices. Primarily materials based on carbon nanostructures or polymer–carbon nanocomposites have been explored for this application. Herein, significantly enhanced THz shielding efficiencies for 2D titanium carbide (Ti3 C2 MXene) thin films with nanoscale THz metamaterials are presented. Nanoscale slot antenna arrays with strong resonances at certain frequencies enhance THz electromagnetic waves up to three orders of magnitude in transmission, which in turn enormously increases the shielding performance in combination with MXene films. Drop‐casting of a colloidal solution of MXene (a few micrograms of dry material) can produce an ultrathin film (several tens of nanometers in thickness) on a slot antenna array. Consequently, THz waves strongly localized in the near‐field regime by the slot antenna undergo enhanced absorption through the film with a magnified effective refractive index. Finally, the combination of an ultrathin MXene film and a nano‐metamaterial shows excellent shielding performance in the THz range. Abstract : Greatly enhanced terahertz (THz) shielding efficiencies are presented using nano‐scale THz metamaterials coated by ultrathin film of 2D titanium carbide (MXene). The THz nano‐metamaterials combined with Ti3 C2 T x efficiently block incident THz electromagnetic waves up to three orders of magnitude in transmission, by simply repetitive drop‐casting of MXene thin film.